Competitive heavy metal removal from binary solution - Bašić, Anita (Array, 2020)
The removal of copper and cobalt ions from binary metal solutions on zeolite NaX by ion exchange process was investigated. Experiments were conducted in unbaffled glass reactor with a Rushton turbine as a stirrer. The dependence of ion exchange kinetics and the amount exchanged were tested using different initial concentrations of metal ions in mixtures. The results obtained indicate that the removal efficiency depends on the initial heavy metal concentrations in binary solutions. Experimental kinetics data were analysed using Ritchie and Weber-Morris models. According to AARD values, the rate in this study was reaction-controlled.